The Indigenous Peoples of the Country of the Dunes, central-eastern Pampa (1780-1806) (Quinto Sol, 2013)
The Leu Mapu Indigenous Peoples become visible in different documentation produced from 1780 on the Buenos Aires border and later in the diaries of Justo Molina y Vasconcelos, referring to their journeys through the pampas in 1804 and 1805. These Indigenous Peoples made up the populations called ranqueles as a whole, but they stood out not only because of their location near Salinas Grandes but also because of their singular adaptation to the dune chains existing in the eastern-southerneastern area of the present-day province of La Pampa, and because of the more intense relation they had with such border. Their participation in the surge of violence that took place in the 1770’s decade and beginning of the following allows us to better understand the causes of that process and increases the available knowledge of the complex intergroup and interethnic relations of that time and of the conditions of occupation of a key area in the history of Indigenous Societies: the transitional area that separates the woods of caldenes (Prosopis caldenia) from the eastern herbaceous plain, in the vicinities of the salt deposit.
Keywords: Leu Mapu; interethnic politics; border violence; ranqueles